2010
DOI: 10.1088/0022-3727/43/16/165003
|View full text |Cite
|
Sign up to set email alerts
|

High coercivity cobalt carbide nanoparticles processed via polyol reaction: a new permanent magnet material

Abstract: Cobalt carbide nanoparticles were processed using polyol reduction chemistry that offers high product yields in a cost effective single-step process. Particles are shown to be acicular in morphology and typically assembled as clusters with room temperature coercivities greater than 4 kOe and maximum energy products greater than 20 KJ/m 3 . Consisting of Co 3 C and Co 2 C phases, the ratio of phase volume, particle size, and particle morphology all play important roles in determining permanent magnet properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 16 publications
5
68
1
1
Order By: Relevance
“…However, a knee beside the remanence has been observed at temperature ranges from 50 to 250 K. This knee originated from the decoupling of hard (Co 2 C) and soft (Co 3 C) phases that can be attributed to the differences in magnetocrystalline anisotropy K eff , magnetization M, and exchange constant A. The strong uniaxial anisotropy associated with the hard magnetic phase is capable of preventing the magnetization reversal of the soft regions [10]. These two phases are said to be exchange coupled through the inter-granular grain boundaries which appears strongly at low temperature ranges.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a knee beside the remanence has been observed at temperature ranges from 50 to 250 K. This knee originated from the decoupling of hard (Co 2 C) and soft (Co 3 C) phases that can be attributed to the differences in magnetocrystalline anisotropy K eff , magnetization M, and exchange constant A. The strong uniaxial anisotropy associated with the hard magnetic phase is capable of preventing the magnetization reversal of the soft regions [10]. These two phases are said to be exchange coupled through the inter-granular grain boundaries which appears strongly at low temperature ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Any residual solvent or unreacted salts were removed by washing 3 times with ethanol. Further details are described elsewhere [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CoeC granular films and Co 2 C thin film were fabricated via electron beam evaporation and chemical vapor deposition, respectively [22,23]. Recently, Harris et al have reported the cobalt carbide nanoparticles with a coercivity over 3 kOe at room temperature, fabricated by a direct chemical synthesis method [24]. It was reported that hcp-Co 3 C was synthesized by mechanical alloying method with precursors of cobalt and carbon powders [25].…”
Section: Introductionmentioning
confidence: 99%
“…Co-C granular films and Co 2 C thin film were fabricated via electron beam evaporation and chemical vapor deposition [12,15], respectively. Recently, Harris et al [16] have reported the cobalt carbide nanoparticles with a coercivity over 3 kOe at room temperature, fabricated by a direct chemical synthesis method. Chemical synthesis of cobalt carbide nanostructures is interesting because of its capability to control the crystal growth in a nanometer scale.…”
Section: Introductionmentioning
confidence: 99%